Follow up of favism cases in non-pediatric age group, and discussion of a possible infectious etiology - salah noori dalli-ali (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract: Background and objectives: Favism is an old disease with unknown etiology. it is not studied in non-pediatric age group before. The aim of this study is to follow cases with previous history of favism in non-pediatric age group, and discussion of a possible infectious etiology for its hemolytic episode. Design and setting: A prospective study on cases with previous history of favism in non-pediatric age group and discussion of possible infectious etiology. Patient and method: Between June 2008- April 2011, 38 cases with previous history of favism and aged thirteen year or more in Al-Ramadi city, Iraq, were studded from all aspects regarding their favic episodes and fava beans ingestion. Results: The number of cases was 38, three of them (7.9%) are females, and 35 (92.1%) are males. The mean age is 27.9(13-61). Out of all patients, 31(81.6%) have favism before age of 13y, 35 (92.1%) have their favism in spring, one case (2.6%) had recurrence of favism once only, 33 (86.8%) were ingesting fava bean before favism attack regularly, and 35 (92.1) of the cases resume fava bean ingestion after favism attack, within 1-17 y after their favism attack. No one had history of drug induced hemolytic anemia. Conclusion: Favism possibly is a separate disease from G6PD deficiency disease. Severe form of favism occurs in glucose-6- phosphate dehydrogenase deficient patients, and there may be unrecognized mild form. Recurrence of disease was uncommon on re-ingestion of fava beans. Very likely the cause of favism is an infectious agent as virus.